Autonomous integrity monitoring SRNS using confidence intervals - Ковалевський, Е.О. (Proceedings of National Aviation University (archive), 2009)
The applicability of the method of confidence intervals has been considered for navigation satellites failure detection. The validity of method usage has been approved by mathematical modeling.